LIVING IT UP WITHOUT FALLING DOWN OR WHAT DO WHEN YOUR INTENTIONS ARE BROUGHT DOWN TO EARTH (Fiep Bulletin - online, 2013)
The extension project Animar sem Quedas its developed with the adults and the elderly dwellers of the Residential Village of the Federal University of Rio de Janeiro, and has as goal: prevent the falls and expand the experiences of leisure in the participants. In this work we analyze the Project in your relation with the concepts of health education, health prevention, quality of life and health promotion. Conclude that the health promotion in the Residential Village its an utopia, because our act its limited by specifics materials conditions that, if doesn't reduce our enthusiasm and strength, keeps our foot in the ground.
Keywords: fall prevention; health promotion; Residential Village UFRJ